Chemoenzymatic Late‐Stage Modifications Enable Downstream Click‐Mediated Fluorescent Tagging of Peptides. Issue 16 (10th March 2023) - Colombano, Alessandro; Dalponte, Luca; Dall'Angelo, Sergio; Clemente, Claudia; Idress, Mohannad; Ghazal, Ahmad; Houssen, Wael E.
Abstract: Aromatic prenyltransferases from cyanobactin biosynthetic pathways catalyse the chemoselective and regioselective intramolecular transfer of prenyl/geranyl groups from isoprene donors to an electron‐rich position in these macrocyclic and linear peptides. These enzymes often demonstrate relaxed substrate specificity and are considered useful biocatalysts for structural diversification of peptides. Herein, we assess the isoprene donor specificity of the N1‐tryptophan prenyltransferase AcyF from the anacyclamide A8P pathway using a library of 22 synthetic alkyl pyrophosphate analogues, of which many display reactive groups that are amenable to additional functionalization. We further used AcyF to introduce a reactive moiety into a tryptophan‐containing cyclic peptide and subsequently used click chemistry to fluorescently label the enzymatically modified peptide. This chemoenzymatic strategy allows late‐stage modification of peptides and is useful for many applications. Abstract : The promiscuity of N1‐tryptophan prenyltransferase AcyF was screened with 22 unnatural pyrophosphates, which exhibited reactive groups suitable for copper‐catalyzed azide‐alkyne cycloaddition, metathesis, and inverse‐electron‐demand Diels‐Alder (IEDDA) reactions. A 10‐mer tryptophan‐containing macrocyclic peptide was tailored by AcyF, and the resulting modified peptide was successfully labelled with a tetrazine–fluorescein conjugate by IEDDA.